«Jewish» social work and its contribution to the general Social Work setting as a profession and discipline. A first scientific-philosophical approach - Hidalgo Lavié, Alfredo (Cuadernos de Trabajo Social, 2014)
The origins of social work have traditionally been linked, outside our borders, with Protestant thought. The diversity of Christian denominations in particular and religious groups in general is a sign of American identity. Religion is not just a view of life that determines patterns of behavior, it is also a way of thinking and its process may or may not allo for innovation and creativity, as well their explanation. The influence of Jewish thought on the future of Social work invites to approach this dilettante question: why is the pre-professional Social work developed that way?
Keywords: Jewish social work; social service; professional approach; charity; public responsibility